CUL4B Promotes Temozolomide Resistance in Gliomas by Epigenetically Repressing CDNK1A Transcription - Ye, Xiang; Liu, Xiaochen; Gao, Min; Gong, Li; Tian, Fei; Shen, Yangli; Hu, Huili; Sun, Gongping; Zou, Yongxin; Gong, Yaoqin (Frontiers in Oncology, 2021)
Resistance to temozolomide (TMZ), the first-line chemotherapeutic drug for glioblastoma (GBM) and anaplastic gliomas, is one of the most significant obstacles in clinical treatment. TMZ resistance is regulated by complex genetic and epigenetic networks. Understanding the mechanisms of TMZ resistance can help to identify novel drug targets and more effective therapies. CUL4B has been shown to be upregulated and promotes progression and chemoresistance in several cancer types. However, its regulatory effect and mechanisms on TMZ resistance have not been elucidated. The aim of this study was to decipher the role and mechanism of CUL4B in TMZ resistance. Western blot and public datasets analysis showed that CUL4B was upregulated in glioma specimens. CUL4B elevation positively correlated with advanced pathological stage, tumor recurrence, malignant molecular subtype and poor survival in glioma patients receiving TMZ treatment. CUL4B expression was correlated with TMZ resistance in GBM cell lines. Knocking down CUL4B restored TMZ sensitivity, while upregulation of CUL4B promoted TMZ resistance in GBM cells. By employing senescence β-galactosidase staining, quantitative reverse transcription PCR and Chromatin immunoprecipitation experiments, we found that CUL4B coordinated histone deacetylase (HDAC) to co-occupy the CDKN1A promoter and epigenetically silenced CDKN1A transcription, leading to attenuation of TMZ-induced senescence and rendering the GBM cells TMZ resistance. Collectively, our findings identify a novel mechanism by which GBM cells develop resistance to TMZ and suggest that CUL4B inhibition may be beneficial for overcoming resistance.